Aptamer-functionalized quercetin thermosensitive liposomes for targeting drug delivery and antitumor therapy. (1st November 2022) - Li, Jian; Gao, Yanting; Liu, Shihe; Cai, Jiahui; Zhang, Qing; Li, Kun; Liu, Zhiwei; Shi, Ming; Wang, Jidong; Cui, Hongxia
Abstract: Chemo-thermotherapy, as a promising cancer combination therapy strategy, has attracted widespread attention. In this study, a novel aptamer functionalized thermosensitive liposome encapsulating hydrophobic drug quercetin was fabricated as an efficient drug delivery system. This aptamer-functionalized quercetin thermosensitive liposomes (AQTSL) combined the merits of high-loading yield, sustained drug release, long-term circulation in the body of PEGylated liposomes, passive targeting provided by 100–200 nm nanoparticles, active targeting and improved internalization effects offered by AS1411 aptamer, and temperature-responsive of quercetin release. In addition, AQTSL tail vein injection combined with 42 °C water bath heating on tumor site (AQTSL + 42 °C)treatment inhibited the tumor growth significantly compared with the normal saline administration ( p < 0.01), and the inhibition rate reached 75%. Furthermore, AQTSL + 42 °C treatment also slowed down the tumor growth significantly compared with QTSL combined with 42 °C administration ( p < 0.05), confirming that AS1411 decoration on QTSL increased the active targeting and internalization effects of the drug delivery system, and AS1411 aptamer itself might also contribute to the tumor inhibition. These data indicate that AQTSL is a potential carrier candidate for different hydrophobic drugs and tumor targeting delivery, and this kind of targeted drug delivery system combined with temperature responsive drug release mode is expected to achieve an ideal tumor therapy effect.